Neurocognitive risk markers in first-episode major depressive disorder with positive family history: a large-scale case–control study - Li, Zhiyong; Pan, Min; Zhang, Xulai; Wang, Anzhen; Fang, Wenmei; Guan, Jianjun; Zhang, Boyu; Cheng, Xialong (Frontiers in Psychiatry, 2026)
ObjectiveTo identify specific neurocognitive risk markers in first-episode major depressive disorder (MDD) patients with positive family history (PFH).MethodsAntipsychotic-naive adults aged 18–60 were recruited across three groups: major depressive disorder patients with positive family history (PFH-MDD, n = 171), major depressive disorder patients with negative family history (NFH-MDD, n = 185), and healthy controls (HCs, n = 180). All patients met the DSM-5 criteria for first-episode MDD (HAMD-24 ≥ 17). Neurocognition was assessed with the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). Group differences were examined using the Kruskal–Wallis test and ANCOVA. Logistic regressions identified independent cognitive predictors; ROC curves evaluated discriminative validity.ResultsThe RBANS total and domain scores differed across the groups (p < 0.001). PFH-MDD performed worse than NFH-MDD in language function (p < 0.001) and total score (p < 0.001). In the PFH group, language function score was negatively correlated with HAMD score (r = −0.184, p = 0.016). In the NFH group, language function score was positively correlated with HAMA score (r = 0.402, p < 0.001) and negatively correlated with HAMD score (r = −0.364, p < 0.001). Total score was negatively correlated with HAMD score (r = −0.158, p = 0.032). After adjustment, language function (OR = 0.82, p = 0.042) and total score (OR = 0.90, p < 0.001) independently predicted PFH-MDD; only total score predicted NFH-MDD (OR = 0.77, p < 0.001). The ROC-AUC values for PFH-MDD were as follows: language = 0.967 and total score = 0.991. Gender × group interactions were non-significant.ConclusionsLanguage dysfunction and global cognitive impairment may be independent markers of first-episode MDD with PFH. Early cognitive profiling may facilitate targeted prevention in high-risk relatives.